Enhancing the Energy Efficiency of the Combined Forging Operations of Upsetting and Drawing out - Kolisnyk K.D.; Chukhlib V.L. (Problems of the Regional Energetics, 2025)
The study investigates the influence of upsetting and drawing out forging parameters on the quality of hook forging and the energy efficiency of these processes. The quality indicators of forged hooks include uneven strain distribution, which leads to a non-uniform distribution of the mechanical properties of the product. The forging technology of hooks was analyzed, and it was determined that the main technological forging operations causing uneven deformation distribution are the sequential upsetting and drawing out processes. Since the influence of specific parameters of these operations remains insufficiently studied, this research was conducted to compare and determine the effect of upsetting and drawing out parameters when performed sequentially in order to improve the mechanical properties of forged hook metal. The modeling was carried out using the QForm engineering software package. To study the distribution of the mechanical properties of the metal, a method for assessing deformation non-uniformity in the cross-section of the forging was applied. Indicators of plastic deformation were considered in one section along the height for upsetting and in one section along the length for drawing out. Additionally, graphs of the deformation non-uniformity coefficient distribution during upsetting and drawing out of the billets were constructed. It was determined that the optimal shape factor for upsetting is h/D = 2. In this case, deformation non-uniformity is reduced by 60%. For drawing out with prior upsetting, the optimal shape factor is also h/D=2 with a strain degree of ℇ=20%. The analysis showed that deformation non-uniformity is reduced by 54%. Additionally, the energy efficiency of the processes was analyzed: with h/D=2, energy consumption during upsetting is reduced by 20–25%, and for drawing with h/D=2 and ℇ=20%, the third pass (2.838 MN) is the least energy-intensive, providing an energy saving of 25–30%.